Hymns of Guru Nanak - Khushwant Singh; Arpita Singh (Orient Longman, 1991)
An important post-colonial novelist writing in English, Singh is best known for his trenchant secularism, his humor, and an abiding love of poetry. His comparisons of social and behavioral characteristics of Westerners and Indians are laced with acid wit.
Keywords: Life of Guru Nanak; Hymns from Raga Asa..